Bio-molecular sensors based on guided mode resonance filters. (August 2016) - Saleem, M. R.; Ali, R.; Honkanen, S.; Turunen, J.
Abstract: In this work a low surface roughness and homogenous, high refractive index, and amorphous TiO2 layer on corrugated structures of diffractive optical element is coated by Atomic Layer Deposition (ALD) for biosensors. The design of Guided Mode Resonance Filters (GMRFs) is based on refractive indices and thicknesses of the waveguide biomolecular layers. The designed spectral shifts are calculated by Fourier Modal Method (FMM) and depend on the magnitude of the variations in refractive index of the biomolecular layer on waveguide structures. Furthermore, the sensitivity of the biomolecular sensors depends on the thickness of biomolecular layer and periodicity of the structures. The waveguide structures designed for larger periods show an enhancement in the sensitivity (nm/RIU) of the biomolecular sensor at longer wavelengths. The periodicities of nanophotonic structures are varied from 300 to 500 nm in design calculations with predominance of increase in effective index of the structure to support leaky waveguide modes.